2011
DOI: 10.1063/1.3643720
|View full text |Cite
|
Sign up to set email alerts
|

Microwave measurements of proton tunneling and structural parameters for the propiolic acid–formic acid dimer

Abstract: Microwave spectra of the propiolic acid-formic acid doubly hydrogen bonded complex were measured in the 1 GHz to 21 GHz range using four different Fourier transform spectrometers. Rotational spectra for seven isotopologues were obtained. For the parent isotopologue, a total of 138 a-dipole transitions and 28 b-dipole transitions were measured for which the a-dipole transitions exhibited splittings of a few MHz into pairs of lines and the b-type dipole transitions were split by ~580 MHz. The transitions assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…Recently, rotational spectroscopy has been used to investigate several of these dimers in the gas phase, which allows the description of several interesting features: 1) tunneling splittings, due to the concerted double proton transfer connecting two equivalent forms; [1][2][3][4] 2) conformational equilibria when the proton transfer, or other feasible large-amplitude motion, connects different configurations of the complex; [5][6][7][8][9][10] and 3) the Ubbelohde effect, [11] which is the structural change of the bimolecular system upon OH!OD isotopic substitution. Recently, rotational spectroscopy has been used to investigate several of these dimers in the gas phase, which allows the description of several interesting features: 1) tunneling splittings, due to the concerted double proton transfer connecting two equivalent forms; [1][2][3][4] 2) conformational equilibria when the proton transfer, or other feasible large-amplitude motion, connects different configurations of the complex; [5][6][7][8][9][10] and 3) the Ubbelohde effect, [11] which is the structural change of the bimolecular system upon OH!OD isotopic substitution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, rotational spectroscopy has been used to investigate several of these dimers in the gas phase, which allows the description of several interesting features: 1) tunneling splittings, due to the concerted double proton transfer connecting two equivalent forms; [1][2][3][4] 2) conformational equilibria when the proton transfer, or other feasible large-amplitude motion, connects different configurations of the complex; [5][6][7][8][9][10] and 3) the Ubbelohde effect, [11] which is the structural change of the bimolecular system upon OH!OD isotopic substitution. Recently, rotational spectroscopy has been used to investigate several of these dimers in the gas phase, which allows the description of several interesting features: 1) tunneling splittings, due to the concerted double proton transfer connecting two equivalent forms; [1][2][3][4] 2) conformational equilibria when the proton transfer, or other feasible large-amplitude motion, connects different configurations of the complex; [5][6][7][8][9][10] and 3) the Ubbelohde effect, [11] which is the structural change of the bimolecular system upon OH!OD isotopic substitution.…”
Section: Introductionmentioning
confidence: 99%
“…This complication takes place, for example, in complexes involving trifluoroacetic acid. [3] Tunneling doubling has also been measured in some hetero-dimers, such as formic acid-propriolic acid, [1] formic acid-acetic acid, [2] and benzoic acid-formic acid. However, tunneling splittings in this complex have been observed when using techniques other than microwave (MW) spectroscopy, such as femtosecond degenerate four-wave mixing and Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…These frequencies were not acid-formic acid dimer. 2,3 These transitions would provide a more direct measure of ∆E, the tunneling frequency, but are likely too weak to obtain in this large complex. Both acrylic acid-homodimer and 3F-benzoic homodimer have the symmetry axis as the b-axis which is the component of the non-zero permanent dipole.…”
Section: -Fluorobenzoic Acid Dimermentioning
confidence: 99%
“…Since the publication of results for the formic acid homodimer measurements in the infrared by Havenith et al, 1 there have been studies made on heterodimers in the microwave region and one study on a homodimer. A permanent dipole moment allows the study by rotational spectroscopy and the following systems have been reported: propiolic acid-formic acid, [2][3][4] acetic acid-formic acid, 5 formic acid-fluoroacetic acid, 6 formic acid-trifluoroacetic acid, and acetic acid-trifluoroacetic acid, 7 formic acid-benzoic acid, 8 and more recently the dimers of acrylic acid with fluoroacetic acid. 9 The analysis of the homodimer of acrylic acid 10 demonstrated proton tunneling amongst identical molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of results for the formic acid homodimer measurements in the infrared by Havenith et al, 1 there have been studies made on heterodimers in the microwave region and one study on a homodimer. A permanent dipole moment allows the study by rotational spectroscopy and the following systems have been reported: propiolic acid-formic acid, [2][3][4] acetic acid-formic acid, 5 formic acid-fluoroacetic acid, 6 formic acid-trifluoroacetic acid, and acetic acid-trifluoroacetic acid, 7 formic acid-benzoic acid, 8 and more recently the dimers of acrylic acid with fluoroacetic acid. 9 The analysis of the homodimer of acrylic acid 10 demonstrated proton tunneling amongst identical molecules.…”
Section: Introductionmentioning
confidence: 99%